2005
DOI: 10.1001/archsurg.140.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes During Laparoscopic Gastric Bypass Procedures

Abstract: Significant detrimental intra-operative hemodynamic and respiratory changes occur in the morbidly obese during laparoscopic gastric bypass. Design: Case series. Setting: Tertiary care university hospital. Patients: Thirteen patients, 10 women and 3 men, undergoing uncomplicated laparoscopic gastric bypass for morbid obesity. Interventions: Using a pulmonary artery catheter and an arterial line, we intraoperatively monitored hemodynamic and respiratory parameters. Parameter values were recorded at set points of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 20 publications
8
23
1
Order By: Relevance
“…Stroke volume (SV) of our patients [1], calculated from stroke volume index (SVI), according to the formula SV= SVI×BSA (Mosteller-derived), is similar to the data of Dumont et al [4] until MAP and HR do not diverge from ours, while the data of Nguyen et al [5] and Artuso et al [3] are different from ours [1] and similar between themselves, as shown on Table 1 (we prefer to analyze stroke volume instead of cardiac index because the latter is directly related to heart rate). Our systemic vascular resistance (SVR), calculated from systemic vascular resistance index (SVRI) according to the formula SVR=SVRI/BSA, is very different from Nguyen et al [5] and Artuso et al [3] and slightly different from Dumont et al [4] ( Table 1).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Stroke volume (SV) of our patients [1], calculated from stroke volume index (SVI), according to the formula SV= SVI×BSA (Mosteller-derived), is similar to the data of Dumont et al [4] until MAP and HR do not diverge from ours, while the data of Nguyen et al [5] and Artuso et al [3] are different from ours [1] and similar between themselves, as shown on Table 1 (we prefer to analyze stroke volume instead of cardiac index because the latter is directly related to heart rate). Our systemic vascular resistance (SVR), calculated from systemic vascular resistance index (SVRI) according to the formula SVR=SVRI/BSA, is very different from Nguyen et al [5] and Artuso et al [3] and slightly different from Dumont et al [4] ( Table 1).…”
supporting
confidence: 82%
“…From an analysis of MAP and HR in reviewed studies, we can observe how [3][4][5] these values present different trends compared with our results (Table 1).…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…Other methods, if to be accepted as an equivalent or replacement for TDCO, must provide a small bias and reproducibility error, and limits of agreement within ±30%. In the face of this, Forfori et al trivialize the studies of Nguyen et al [3] and Artuso et al [4], which both used TDCO as their test method to determine CO and the derived indices of cardiac index (CI) stroke volume SV, stroke index (SI) and systemic vascular resistance (SVR) and SVRI. Alleging equivalence to TDCO, the authors emphasize that their results for SV are similar to those of Dumont et al [5], which are, on the mean, 64 and 72 mL, respectively.…”
mentioning
confidence: 99%